Effects of short sprint interval training on aerobic and anaerobic indices: A systematic review and meta-analysis - Boullosa, D.; Dragutinovic, B.; Feuerbacher, J.; Benítez-Flores, S.; Coyle, E.; Schumann, M. (Scandinavian Journal of Medicine & Science in Sports, 2022)
The effects of short sprint interval training (sSIT) with efforts of =10 s on maximal oxygen consumption (VO2max), aerobic and anaerobic performances remain unknown. To verify the effectiveness of sSIT in physically active adults and athletes, a systematic literature search was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The databases PubMed/MEDLINE, ISI Web of Science, and SPORTDiscus were systematically searched on May 9, 2020, and updated on September 14, 2021. Inclusion criteria were based on PICO and included healthy athletes and active adults of any sex (=40 years), performing supervised sSIT (=10 s of "all-out" and non-"all-out" efforts) of at least 2 weeks, with a minimum of 6 sessions. As a comparator, a non-sSIT control group, another high-intensity interval training (HIIT) group, or a continuous training (CT) group were required. A total of 18 studies were deemed eligible. The estimated SMDs based on the random-effects model were -0.56 (95% CI: -0.79, -0.33, p < 0.001) for VO2max, -0.43 (95% CI: -0.67, -0.20, p < 0.001) for aerobic performance, and -0.44 (95% CI: -0.70, -0.18, p < 0.001) for anaerobic performance after sSIT vs. no exercise/usual training. However, there were no significant differences (p > 0.05) for all outcomes when comparing sSIT vs. HIIT/CT. Our findings indicate a very high effectiveness of sSIT protocols in different exercise modes (e.g., cycling, running, paddling, and punching) to improve VO2max, aerobic, and anaerobic performances in physically active young healthy adults and athletes.